Academic resilience : personal stories and lessons learnt from the COVID-19 experience - Mahat, Marian; Blannin, Joanne; Cohrssen, Caroline; Reyes, Elizer Jay de Los (Surviving and thriving in academia, 2022)
The COVID-19 pandemic undoubtedly tested the resilience of academics in higher education. Many universities were severely affected by reduced student enrolment, with widespread job losses reported across universities. For many academics, the impact of the pandemic has been worrying, financially crippling and overwhelming. The virus has also exposed academic inequalities and impacted heavily on vulnerable people. The individual and collective heroic spirit of many academics has been nothing short of extraordinary. Overcoming the initial hurdles of COVID-19 takes one kind of energy; the resilience needed to remain engaged despite the continuing changes and uncertainties is quite another challenge. It is one that demands sustained resilience. This timely book provides perspectives across disciplines, career stages and global contexts on how to develop resilience in academia. These personal stories may empower others not only to survive, but to thrive in times of adversity.